2000
DOI: 10.1017/s0021859699007583
|View full text |Cite
|
Sign up to set email alerts
|

Influence of time of sowing and last cut for fodder on the fodder and seed yields of Egyptian clover

Abstract: Field investigations were conducted during the winter seasons of 1992/93 and 1993/94 to find the optimum sowing time and time of last fodder cut for the fodder and seed production of Egyptian clover (Trifolium alexandrinum L.). The delay in sowing from 1 October to 15 November decreased the green and dry fodder yields but increased the seed yields. Total green and dry fodder yields (of all cuttings) for 1 or 15 October sowings were significantly higher than the 15 November sowing in both years and 1 Novem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 0 publications
8
21
0
Order By: Relevance
“…In fact, postponing the cut (until the first sign of green buds) compared with cutting when the basal shoots were 3 cm long resulted in poorer regrowth, fewer heads per unit area, fewer seeds per head, and a lower seed yield. These results confirm the significant negative relationship between the date of the last cut for fodder and the seed yield observed in berseem by Lowe and Bowdler (1982), Stringi et al (1987), and Sardana and Narwal (2000). However, moving the cutting date up (to when basal shoots were 1 cm long) resulted in less weed control and a lower seed yield.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, postponing the cut (until the first sign of green buds) compared with cutting when the basal shoots were 3 cm long resulted in poorer regrowth, fewer heads per unit area, fewer seeds per head, and a lower seed yield. These results confirm the significant negative relationship between the date of the last cut for fodder and the seed yield observed in berseem by Lowe and Bowdler (1982), Stringi et al (1987), and Sardana and Narwal (2000). However, moving the cutting date up (to when basal shoots were 1 cm long) resulted in less weed control and a lower seed yield.…”
Section: Discussionsupporting
confidence: 88%
“…In all genotypes and years of this experiment, cumulative dry forage biomass levels increased with each subsequent cut, with the highest DM yield being achieved with Agaitti Berseem-2002 (13.4 t/ha), which was 46% higher than LBF1 and 30% higher than LBM1. This is consistent with the findings of a significant increase in DM forage yield which occurred with the addition of every forage cut of berseem clover in an Indian trial 7 . Similarly, a 26% increase in DM production was also reported by using improved cultivars 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Berseem growers have mostly planted this as a dual purpose crop for both forage and seed production 6 . There are different yield components attributed towards berseem crop yield but the genotype and harvesting management are the key factors in obtaining quality forage and seed yields 7,8 . However, scientific information is still lacking regarding the effects of genotypes, and different forage cutting regimens on the forage and seed yields as well as on the nutritive values of berseem forage.…”
mentioning
confidence: 99%
“…In both years, the berseem clover DM and protein yields obtained at the Cut 2 (first berseem clover regrowth) were greater than those at the Cut 3 or Cut 4, disagreeing with results reported by El‐Bably (2002) who found that DM yield of berseem clover sole crop increased from the Cut 2 to Cut 3. The earlier planting of berseem clover during that experiment (in November) and the longer duration of the vegetative phase could be attributed for this difference (Sardana and Narwal, 2000). In Year 1, the berseem clover regrowth was greater in berseem clover sole crop (total DM 19.2 Mg ha −1 ) as compared with the intercrop treatments (total DM 10.9–15.8 Mg ha −1 ).…”
Section: Resultsmentioning
confidence: 93%
“…Berseem or Egyptian clover is an annual legume that is a vine with climbing growth habit, great productivity due to its high growth rate and good fodder recovery after cutting, and high levels of CP. It is well adapted to a range of environments and is usually grown in the Mediterranean, central European, and southeast Asian countries for forage production (Sardana and Narwal, 2000; Iannucci, 2001; El‐Bably, 2002; de Santis et al, 2004). Berseem clover is the second, after alfalfa ( Medicago sativa L.), most important and profitable legume in Greece used for forage production mainly in fields that cannot be irrigated during summer (NSSG, 2007).…”
mentioning
confidence: 99%